Determination of Total Phenolics, Flavonoids, and Antioxidant Activity and GC-MS Analysis of Malaysian Stingless Bee Propolis Water Extracts - Sharifah Nur Amalina Syed Salleh; Nur Ayuni Mohd Hanapiah; Hafandi Ahmad; Wan Lutfi Wan Johari; Nurul Huda Osman; Mohd Razif Mamat (Scientifica)
Propolis contains polyphenolic compounds such as flavonoids and phenols that are able to demonstrate a broad spectrum of biological activities including antioxidant, antibacterial, and many more. This study was carried out to determine the total phenolics, flavonoids, and antioxidant activity of water-extracted propolis samples from three different Indo-Malayan stingless bee species, namely, Tetrigona apicalis, Tetrigona binghami, and Homotrigona fimbriata. Total phenolic and flavonoid contents were evaluated using Folin–Ciocalteu colorimetric and aluminium chloride methods, respectively, while the antioxidant activity was analysed using 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay. Results indicated that H. fimbriata extracts exhibit the highest TPC, TFC, and antiradical activity among all samples tested. Interestingly, the data also showed that the higher the concentration of the extract used, the higher the antioxidant activity exhibited by the samples. Statistically, there were no significant differences recorded between the different bee species’ propolis studied. In conclusion, the propolis extracts showed stronger antioxidant potential with higher TPC and TFC values. This study also noted the presence of bioactive compounds from local stingless bee propolis that could potentially be utilised for their medicinal and health benefits.